2012
DOI: 10.1002/er.2923
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of ion transport reactor for oxy-fuel combustion

Abstract: SUMMARY This paper aims at investigating the performance of a cylindrical ion transport reactor designed for oxy‐fuel combustion. The cylindrical reactor walls are made of dense, nonporous, mixed‐conducting ceramic membranes that only allow oxygen permeation from the outside air into the combustion chamber. The sweep gas (CO2 and CH4) enters the reactor from one side and mixes with the oxygen permeate, and the products are discharged from the other side. The process of oxygen permeation through the reactor wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Figure 20 presents the mass fraction distribution of 0 2 in the permeate side of the ITM for increasing ratios of O2/N2 mixture. [17,18,23] that confirm the above stated results. The high values of mass fractions at the edges may be attributed to the possible accumulation of oxygen molecules due to lower sweep gas velocities as can be seen from Fig.…”
Section: Comparison Of Experimental and Numerical Resultssupporting
confidence: 86%
“…Figure 20 presents the mass fraction distribution of 0 2 in the permeate side of the ITM for increasing ratios of O2/N2 mixture. [17,18,23] that confirm the above stated results. The high values of mass fractions at the edges may be attributed to the possible accumulation of oxygen molecules due to lower sweep gas velocities as can be seen from Fig.…”
Section: Comparison Of Experimental and Numerical Resultssupporting
confidence: 86%
“…Therefore, the flow is laminar. Many combustion studies [32,33,55] omit the use of radiation models in their investigations either because its role is less important or to save computational time. The effect of radiation in the case considered here may be important because of the use of wider channels as shown next.…”
Section: Resultsmentioning
confidence: 99%
“…Their studies paved the way to research on synthesis and analysis of LSCF membranes [14]. Farooqui et al [15] modeled cylindrical ion transport reactor for co-current and counter current flows and found that oxygen to fuel mass ratio increases as the percentage of CO 2 increases in the sweep gas. In a series of papers, Hong et al [16e18] developed accurate and comprehensive analysis of the coupling between heat and mass transfer on both sides of the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of combustion, heat transfer, burnout, pollutants, and slagging under oxy‐fuel combustion (Oxy) conditions are very different from those under air combustion (Air) conditions. Many scholars have studied the coal combustion and pollutant emission characteristics of oxy‐fuel boilers . However, there has been little information about the deposition characteristics of ash .…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have studied the coal combustion and pollutant emission characteristics of oxy-fuel boilers. [6][7][8][9][10][11][12][13][14][15][16] However, there has been little information about the deposition characteristics of ash. 17,18 Coal contains a certain amount of inorganic material.…”
Section: Introductionmentioning
confidence: 99%